Comprehensive morphometry of subcortical grey matter structures in early-stage Parkinson's disease. - Menke, R; Szewczyk-Krolikowski, K; Jbabdi, S; Jenkinson, M; Talbot, K; Mackay, C; Hu, M (2014)
Previous imaging studies that investigated morphometric group differences of subcortical regions outside the substantia nigra between non-demented Parkinson's patients and controls either did not find any significant differences, or reported contradictory results. Here, we performed a comprehensive morphometric analysis of 20 cognitively normal, early-stage PD patients and 19 matched control subjects. In addition to relatively standard analyses of whole-brain grey matter volume and overall regional volumes, we examined subtle localized surface shape differences in striatal and limbic grey matter structures and tested their utility as a diagnostic marker. Voxel-based morphometry and volumetric comparisons did not reveal significant group differences. Shape analysis, on the other hand, demonstrated significant between-group shape differences for the right pallidum. Careful diffusion tractography analysis showed that the affected parts of the pallidum are connected subcortically with the subthalamic nucleus, the pedunculopontine nucleus, and the thalamus and cortically with the frontal lobe. Additionally, microstructural measurements along these pathways, but not along other pallidal connections, were significantly different between the two groups. Vertex-wise linear discriminant analysis, however, revealed limited accuracy of pallidal shape for the discrimination between patients and controls. We conclude that localized disease-related changes in the right pallidum in early Parkinson's disease, undetectable using standard voxel-based morphometry or volumetry, are evident using sensitive shape analysis. However, the subtle nature of these changes makes it unlikely that shape analysis alone will be useful for early diagnosis.